Immunomodulatory activity of monophosphoryl lipid A in C3H/HeJ and C3H/HeSnJ mice. - Hiernaux, J R (1989)
Treatment with nontoxic monophosphoryl lipid A (MPL) derived from a polysaccharide-deficient, heptoseless Re mutant of either Salmonella typhimurium or Salmonella minnesota R595 enhanced the immunoglobulin M (IgM) anti-type III pneumococcal polysaccharide (SSS-III) antibody response of C3H/HeSnJ mice. Such an adjuvant effect was not observed in lipopolysaccharide-nonresponder C3H/HeJ mice. Nevertheless, C3H/HeJ spleen cells produced a weak mitogenic response to both preparations of MPL in vitro, and C3H/HeJ mice showed a significant increase in serum IgM levels without an increase in numbers of splenic IgM-secreting plaque-forming cells after in vivo treatment with MPL. A significant increase in serum IgG3 levels was accompanied by a transient decrease in serum IgG1 levels in C3H/HeSnJ mice given MPL; such non-antigen-specific polyclonal effects were not observed in C3H/HeJ or in athymic nu/nu mice. Since the enhanced antibody response to SSS-III has been attributed to the inactivation of suppressor T cells by MPL and since suppressor-T-cell activity is demonstrable in both C3H/HeSnJ and C3H/HeJ mice, these findings imply that (i) the suppressor T cells of C3H/HeJ mice are refractory to inactivation by MPL and (ii) some of the polyclonal and mitogenic effects produced in C3H/HeJ mice are due to the direct action of MPL on B lymphocytes.